Digital bridges for human support: a review of online psychological interventions in social work contexts - Cădariu, Ioana-Eva; Rad, Dana (Technium Sustainability, 2025)
The digital transformation of mental health services has swiftly advanced in recent years, significantly impacting social work practice. This review consolidates existing research on digital psychological therapies, including teletherapy, smartphone applications, chatbots, and psychoeducational platforms, as their adoption in social work contexts continues to rise. The study examines outcomes, including symptom reduction, help-seeking behavior, therapeutic alliance, and user satisfaction, through interdisciplinary research across various demographics, such as teenagers, older adults, and individuals with disabilities or chronic illnesses. The review emphasizes practitioner viewpoints on digital tools, the necessity of training in ethical digital practices, and the dangers of burnout and boundary erosion in distant service provision. Particular emphasis is placed on equity concerns including digital literacy, access inequities, and cultural adaptation, incorporating regional perspectives from Eastern Europe. Although digital tools have potential opportunities for broadening access and improving psychological assistance, their appropriate implementation necessitates human-centered design, ongoing assessment, and adherence to social work principles. This study promotes a hybrid future where digital innovation enhances—rather than supplants—relational, inclusive, and sustainable care.